Central retinal vein occlusion in young population: risk factors and outcomes - Berguig, Jordan; Abdelmassih, Youssef; Azar, Georges; Lafolie, Justine; Alonso, Anne Sophie; Bonnin, Sophie; Vasseur, Vivien; Mauget-Faysse, Martine (Frontiers in Medicine, 2023)
Objective To evaluate the risk factors and outcomes of central retinal vein occlusion (CRVO) in young patients (< 40 years). Methods In this retrospective monocentric case series, we included young patients (<40 years) with CRVO. Patients’ medical files were analyzed focusing on demographic characteristics, suspected risk factors, ophthalmic work-up, visual acuity (VA), treatment, and outcomes. Results A total of 54 eyes of 52 patients were included. Central retinal vein occlusion was considered idiopathic in 13 patients (25%). The main risk factors identified were ocular hypertension (20.4%), inflammation (20.4%), high blood pressure (14.8%), and coagulation abnormality (11.1%). Final VA was lower in patients with high blood pressure and inflammation when compared to patients with no risk factor (p = 0.03 and 0.04, respectively). Intravitreal injections were needed in 23 eyes (42.6%) and 19 eyes (35.2%) received panretinal photocoagulation treatment. Conclusion Central retinal vein occlusion is frequently associated with risk factors in young patients (75% of patients). In addition to the usual factors found in older patients, such as ocular hypertension and high blood pressure, coagulation abnormality and inflammation were also among the risk factors identified. Young patients with CRVO should be evaluated for the presence of risk factors and patients with high blood pressure or inflammatory findings should be followed carefully since they have a worse outcome.